Bisphosphonates and their Role in Therapy for Breast Cancer – Results from the PATH Biobank - Fick, E.-M.; Anzeneder, T.; Katalinic, A.; Waldmann, A. (Geburtshilfe und Frauenheilkunde, 2013)
Introduction: Bisphosphonates are well known above all for their use in the treatment of osteoporosis. They also play an important role as accompanying therapy for advanced tumour diseases with extensive spread into the skeletal system. Their adjuvant use in the treatment of breast cancer without bony metastases is currently a subject of controversial discussion. The objective of the present evaluation is to describe the use of bisphosphonates in the therapy for breast cancer. We will show how frequently bisphosphonates are used, which bisphosphonates are preferred and what specific features patients under bisphosphonate therapy exhibit. Methods and Materials: The pseudonymous data set from the biobank of the German PATH foundation was used for the evaluation. From the total collective, 2492 patients were selected after consideration of the inclusion and exclusion criteria. The selected patient collective was divided into two groups (with and without bisphosphonate therapy) and the two groups compared with one another with the help of descriptive statistics. Results: 17.5 % of the 2492 patients had prescriptions for a bisphosphonate as part of their therapy. The most frequently administered bisphosphonate was zoledronate. Pathological (induced by tumour therapy) osteoporosis was the most frequently stated indication among the bisphosphonate patients, followed by consumption starting prior to the breast cancer therapy and treatment of bony metastases. Patients under bisphosphonate and antihormonal therapy frequently received an aromatase inhibitor as the active principle in the antihormonal therapy whereas patients under antihormonal therapy but without bisphosphonates more frequently received tamoxifen as active principle. Ten of the 2492 patients reported receiving bisphosphonate therapy as prophylaxis for bony metastases without a documented and approved indication. Use of bisphosphonates in the course of the GAIN, ICE, SUCCESS or, respectively, NATAN trials was reported by 29 of the 2492 patients. Conclusions: In the PATH collective, bisphosphonates were employed above all for the treatment of (tumour therapy-induced) osteoporosis and bony metastases. Off-label use and participation in clinical trials played only a minor role in this patient collective. Against the background of the uncertain data status for the adjuvant use of bisphosphonates, the development (and use) of standardised, validated questionnaires to record the indications for and frequency of use of bisphosphonate therapy is recommended.
Keywords: bisphosphonates; breast cancer; therapy; biobank